The effects of a 25% discount on fruits and vegetables: results of a randomized trial in a three-dimensional web-based supermarket - Waterlander Wilma E; Steenhuis Ingrid HM; de Boer Michiel R; Schuit Albertine J; Seidell Jacob C (BMC, 2012)
Abstract Background Lowering the price of fruit and vegetables is a promising strategy in stimulating the purchase of those foods. However, the true effects of this strategy are not well studied and it is unclear how the money saved is spent. The aim of this study is to examine the effects of a 25% discount on fruits and vegetables on food purchases in a supermarket environment. Methods A randomized controlled trial with two research conditions was conducted: a control condition with regular prices (n = 52) and an experimental condition with a 25% discount on fruits and vegetables (n = 63). The experiment was carried out using a three-dimensional web-based supermarket, which is a software application in the image of a real supermarket. Data were collected in 2010 in the Netherlands. Participants received a fixed budget and were asked to buy weekly household groceries at the web-based supermarket. Differences in fruit and vegetable purchases, differences in expenditures in other food categories and differences in total calories were analyzed using independent samples t-tests and multiple linear regression models accounting for potential effect modifiers and confounders. Results The purchased amount of fruit plus vegetables was significantly higher in the experimental condition compared to the control condition (Δ984 g per household per week, p = .03) after appropriate adjustments. This corresponds to a 25% difference compared to the control group. Both groups had similar expenditures in unhealthier food categories, including desserts, soda, crisps, candy and chocolate. Furthermore, both groups purchased an equal number of food items and an equal amount of calories, indicating that participants in the discount condition did not spend the money they saved from the discounts on other foods than fruits and vegetables. Conclusion A 25% discount on fruits and vegetables was effective in stimulating purchases of those products and did neither lead to higher expenditures in unhealthier food categories nor to higher total calories purchased. Future studies in real supermarkets need to confirm these findings.